2010
DOI: 10.1007/s12274-010-1016-2
|View full text |Cite
|
Sign up to set email alerts
|

Soluble graphene through edge-selective functionalization

Abstract: Thermally expanded graphite was functionalized with 4-bromophenyl addends using the in situ diazonium formation procedure, and after mild sonication treatment in N,N'-dimethylformamide, thin graphene layers were exfoliated from the bulk graphite. These chemically-assisted exfoliated graphene (CEG) sheets had higher solubility than pristine graphene without any stabilizer additive. More than 70% of these soluble flakes had less than 5 layers. Energy filtered transmission electron microscopy (EFTEM) elemental ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 24 publications
3
88
0
Order By: Relevance
“…1d reveals that RGO exhibits typical transparent and rippled silk morphology. From the folded regions, the number of layers could be identified according to recent reports [16]. The high resolution TEM (HRTEM) image is used to access the number of layers at multiple locations.…”
Section: Resultsmentioning
confidence: 99%
“…1d reveals that RGO exhibits typical transparent and rippled silk morphology. From the folded regions, the number of layers could be identified according to recent reports [16]. The high resolution TEM (HRTEM) image is used to access the number of layers at multiple locations.…”
Section: Resultsmentioning
confidence: 99%
“…38) Therefore, edge selectivity is a key factor on behalf of an effective edge functionalization which is directly related to the degree of exposure of the interior basal planes to the functionalization reagent. 64) Single-and few-layer graphene sheets are also sensitive to their chemical and physical environment which can induce the formation of ripples. The reason for rippling could be attributed to the presence or formation of vacancies and sp 3 bonds, which interrupt the conjugation and make the graphene surface buckle over short ranges.…”
Section: Edge Termination Through Chemical Functionalizationmentioning
confidence: 99%
“…For example, Sun et al 20. concluded that graphite can be changed to graphene by covalent functionalization of the graphite and the synthesis of a stable suspension in the presence of DMF without any added surfactant or stabilizer.…”
mentioning
confidence: 99%